PENGARUH FINANCIAL LITERACY, FINANCIAL INCLUSION, FINANCIAL BEHAVIOR TERHADAP KEPUTUSAN MELAKUKAN PINJAMAN ONLINE - Florencia Irena; Stanislaus Adnanto Mastan (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine the influence of financial literacy, financial inclusion, and financial behavior on the decision to take out peer-to-peer (P2P) lending. The data collection method used in this study is primary data, with purposive sampling method. The questionnaire was distributed to 106 student respondents currently pursuing their education in Surabaya. The data for this research was processed using the Structural Equation Models-Partial Least Square (SEM-PLS) software. The results of this research indicate that financial inclusion and financial behavior have a positive and significant effect on the decision to take out peer-to-peer (P2P) lending. However, financial literacy does not have an influence as it has a hypothesis test result greater than 0.05. The Adjusted R-Square value of 0.474 means that the independent variables contribute to 47.4%, while the remaining 52.6% is influenced by other variables not included in this study